2017
DOI: 10.1002/cyto.a.23265
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative high‐content/high‐throughput microscopy analysis of lipid droplets in subject‐specific adipogenesis models

Abstract: Neutral lipids packed in lipid droplets (LDs) are essential as a source of fuel for organisms, and specialized storing cells, the adipocytes, provide a buffer for energy variations. Many modern-society-disorders are connected with excess accumulation or deficiency of LDs in adipose tissue. Intracellular LD number and size distribution reflect the tissue conditions, while the associated mechanisms and genes rs are still poorly understood. Large-scale genetic screens using human in vitro differentiated primary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In this study, we have demonstrated that human prostatederived CAFs store more neutral lipid in LDs than normal prostate fibroblasts (NFs). Each cell type had a unique LD distribution pattern and size range, which could impact signaling (Welte and Gould, 2017;Bombrun et al, 2017). Normal fibroblasts had a distinct concentric ring of neutral lipids residing close to the nucleus, whereas LDs in CAFs were dispersed throughout the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have demonstrated that human prostatederived CAFs store more neutral lipid in LDs than normal prostate fibroblasts (NFs). Each cell type had a unique LD distribution pattern and size range, which could impact signaling (Welte and Gould, 2017;Bombrun et al, 2017). Normal fibroblasts had a distinct concentric ring of neutral lipids residing close to the nucleus, whereas LDs in CAFs were dispersed throughout the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Image analysis was performed using CellProfiler (www.cellprofiler.org) pipelines (example shown in S1B Fig) for nuclear, cellular and lipid droplets segmentation and measurement extraction. For lipid droplet analysis the following steps were used: images were background subtracted using the rolling ball method; Smooth, IdentifyPrimaryObjects (generates nuclear mask based on smoothed DAPI labeling, its intensity and size), IdentifySecondaryObjects (generates the “cell” mask based on the lipid staining and distance from the nuclear mask–similar to [22]), IdentifyPrimaryObjects (generates the lipid droplet mask by analyzing the Lipidtox stain images using Otsu thresholding and a size filter), IdentifyTertiaryObjects (used to determine the “cytoplasm”, subtracts the nuclear mask from the cell mask), and RelateObjects (relates each lipid droplet mask to the corresponding cytoplasm mask). A much simpler pipeline was used for nuclear protein ( i .…”
Section: Methodsmentioning
confidence: 99%
“…These techniques will further reveal the complex nature of the mechanisms by which extrinsic factors regulate signal transduction and cell-fate decisions of hematopoietic stem cells. In addition to studies in genetic mouse models, transcriptomic and single cell analysis after fluorescence Communication to the Editor activated cell sorting of live cells represent fundamental tools that will help us understand the roles of adipocytes within the bone marrow microenvironment (81)(82)(83)(84). In spite of powerful experimental mouse models providing a proof of concept for adipocytes biology in the bone marrow, we are still lacking direct demonstration of adipocytes roles in the human bone marrow.…”
Section: Perspectives/future Directionsmentioning
confidence: 99%